Vaults, heroes, and enemies: a multimodal approach to poster propaganda in the Fallout series - Aleksić, Dušan; Tasić, Miloš; Stamenković, Dušan (Frontiers in Psychology, 2025)
The Fallout game series has utilized in-game posters as both decorative and narrative elements, which have helped it shape its post-apocalyptic world. These posters often serve as (satirical) propaganda and reflect the societal structures, ideologies, and conflicts of the game’s dystopian setting. This study analyzes all propaganda-themed posters from six Fallout role-playing video games (1997–2018) to examine their multimodal features and propaganda techniques. Using a multimodal framework combined with propaganda studies, we explore how text-image relations, figures of speech, typography, color schemes, and iconography interact with propaganda strategies such as Appeal to emotion and fear, Name-calling, Glittering generalities, and Band wagon. Our findings reveal that text-dominant posters and sans-serif fonts are the most frequent design choices. Metonymy is the most used figure of speech, and it often reinforces ideological symbols, while red and blue emerge as dominant colors, frequently associated with military or nationalistic themes. The study also identifies strong correlations between specific propaganda techniques and multimodal features, demonstrating how visual and textual elements work together to achieve persuasive impact. The study situates Fallout’s posters within a broader context and provides insight into how video games appropriate and adapt real-world propaganda strategies and forms of political messaging.